2023
DOI: 10.1101/2023.11.06.565756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell multi-omic and spatial atlas of B cell lymphomas reveals differentiation drives intratumor heterogeneity

Donnacha Fitzgerald,
Tobias Roider,
Marc Andrea Baertsch
et al.

Abstract: Intratumor heterogeneity is intrinsic to cancer pathogenesis and evolution, although little is known about how it relates to the differentiation trajectories of the tumor’s cell-of-origin. Nodal B-cell non-Hodgkin lymphomas are a diverse set of cancers thought to originate from distinct stages of B-cell maturation. Through a single-cell multi-omic and spatial atlas of diffuse large B-cell, mantle cell, follicular, and marginal zone lymphomas along with reactive lymph nodes (n=51), we found multiple B-cell matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…We leveraged a data integration approach based on mutual nearest neighbors and canonical correlation analysis to map B-cell maturation states from a published single-cell transcriptomic dataset in non-malignant reactive lymph nodes to tumor samples (Extended Data Fig. 9a-b) 33,35 . Restriction of the immunoglobulin light chain among the vast majority of B-cells in each tumor to either kappa or lambda confirmed their monoclonality and therefore malignancy (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We leveraged a data integration approach based on mutual nearest neighbors and canonical correlation analysis to map B-cell maturation states from a published single-cell transcriptomic dataset in non-malignant reactive lymph nodes to tumor samples (Extended Data Fig. 9a-b) 33,35 . Restriction of the immunoglobulin light chain among the vast majority of B-cells in each tumor to either kappa or lambda confirmed their monoclonality and therefore malignancy (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, naïve B-cells (Naïve) undergoing T-cell dependent activation migrate through the dark zone (DZ) and light zone (LZ) of the germinal center where they undergo somatic hypermutation of the B-cell receptor and selection by antigen-presenting cells, followed by maturation into memory B-cells (Mem IgM or Mem IgG) and plasma cells (Plasma) 2932 . While the cell of origin is central to the classification of B-cell lymphomas and other cancers, it was recently shown that cancer cells can retain their ability to differentiate along their innate differentiation trajectory, whereby tumors evolve multiple maturation states from the same cell of origin 33 . Meanwhile, clonal evolution posits that tumors also evolve through the accumulation of heterogenous genetic variants over time resulting in the generation of treatment resistant sub-clones 34 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations